Study of the Leading Causes of Death in Guanajay in the year 2013 - Jorge Julian Sánchez Fernández; Ana Lilia Cabrera Menéndez; Ailed Pérez Pi; José Carlos Merino Concepción (Medisur)
Background: a change in the leading causes of death has been observed in the municipality of Guanajay, Artemisa province, in recent years. The causal structure, considering the ten leading causes of death, has changed compared to previous years. Objective: to describe mortality in the municipality of Guanajay during 2013. Methods: A cross-sectional study of all (158) deaths in Guanajay during 2013 was conducted. In addition to the cause of death, sociodemographic variables (age, sex, skin color) were analyzed. The top three causes of death in the study period were taken from the certificates issued according to the content of the Tenth Revision of the International Classification of Diseases. Results: females (56.96 %) predominated, with a female-to-male ratio of 1.3: 1. The 67-83 age group was the most affected in both sexes. The three leading causes of death were malignant neoplasms, acute myocardial infarction and cerebrovascular disease. The top three locations of tumors were the lungs, colon and prostate. Conclusions: chronic noncommunicable diseases, in particular tumors, caused a higher number of deaths in Guanajay in 2013, which is similar to what happens in other parts of the country.